A constructivist analysis of the bilateral relations between South Africa and China - Muzi Shoba; Victor H. Mlambo (Cogent Social Sciences)
It is no longer debatable that China has become Africa’s most significant trading partner having surpassed the United States and its allies back in 2009 as Africa’s main trade partner in the world. During this period, South Africa has emerged as one of China’s imperative allies in the world and its most important partner in Africa. This article draws on historical secondary data sources and relies on constructivism theory to delineate the evolution of South Africa-China relations. This analysis reveals the range of historical, social, economic and political interests that contributed to the evolution of South Africa-China relations in the manner that it did for the past few decades. This analysis also shows how the relations between South Africa and China have been shaped and influenced by a range of interests and identities in line with constructivism theory postulations. This article discusses the contested phenomenon of whether the relationship between South Africa and China represents symmetrical or asymmetrical cooperation. The article concludes that asymmetry exists in the relations between the two countries in the economic sphere, however, this could not be argued to the same extent in other areas of their engagements. Therefore, it is expected that the two countries will continue to advance their relations despite the criticism against their collaboration, as both remain committed to this relationship anchored on long-shared historical interests and identities.